THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND DIET WITH BLOOD SUGAR LEVELS DURING TYPE 2 DIABETES MELLITUS DURING THE COVID-19 PANDEMIC IN THE WORKING AREA OF THE MAKRAYU PALEMBANG HEALTH CENTER IN 2021: - - Azwaldi, Azwaldi; Sulistini, Rumentalia; Oktariyanti, Syafhira (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
ABSTRACT Background: Diabetes is the second most common comorbidity due to the decline in the immune function of diabetics is one of the factors triggering the ease of COVID-19 during this pandemic. Lifestyle changes can trigger an increase in diabetes mellitus; some of these lifestyles are physical activity and diet. Purpose: This study aimed to determine the relationship between physical activity and diet with blood sugar levels during Type 2 Diabetes Mellitus during the COVID-19 Pandemic in the Makrayu Health Center Palembang Working Area in 2021.Using a cross-sectional approach. Methods: Sampling in this study is a purposive sampling technique with as many as 53 respondents. Data collection using Baecke's questionnaire and diet questionnaire. The results of the analysis using the Mann-Whitney test. The results of this study indicate that 68.8% are female, the average age of the respondents is 59.77 years, and the average length of the suffering of the respondents is 5.28 years. 22.6% of respondents with a history of DM. 52.8% of mild physical activity, 49.1% of respondents with poor diet, average blood sugar when respondents were 250.19 mg/dl. Results: The results of the analysis of physical activity with temporary blood sugar levels (P-Value 0.001) and analysis of eating patterns with temporary blood sugar levels (P-Value 0.0005). Someone with light physical activity and a poor diet can increase blood sugar levels. Conclusion: The results of this study can be input for health workers to provide education about the importance of doing regular physical activity and maintaining a diet to increase physical activity and a good diet for people with type 2 diabetes mellitus. Keywords: Diabetes Mellitus; Physical Activity; Diet; Blood Sugar;